In situ atomic-scale observation of oxidation and decomposition processes in nanocrystalline alloys - Jinming Guo (Nature Portfolio, 2018)
Oxygen contamination during the mixing of precursor powders for nanocrystalline materials affects alloy microstructure, but exactly how remains unclear. Here, the authors show that stable nano-oxides can form easily inside severely deformed Cu-Fe grains during heating.